Long-term survival after repetitive lymphadenectomy for nodal recurrence of pancreatic neuroendocrine neoplasms: a report of two cases. Issue 10 (13th October 2021) - Hane, Yuma; Tsuchikawa, Takahiro; Takeuchi, Satoshi; Tanaka, Kimitaka; Nakanishi, Yoshitsugu; Asano, Toshimichi; Noji, Takehiro; Kurashima, Yo; Ebihara, Yuma; Murakami, Soichi; Nakamura, Toru; Okamura, Keisuke; et al.
Abstract: Pancreatic neuroendocrine neoplasms (PNENs) are rare, but their incidence has increased in recent years. Curative surgery is recommended in several global guidelines for resectable PNENs. Lymph node recurrence after R0 resection for PNENs is infrequent, and global guidelines recommend surgical resection for recurrence, if resectable. However, data on the prognosis after surgical resection for nodal recurrence of PNENs are limited. We herein report two cases in which long-term survival was achieved after repetitive lymphadenectomy for nodal recurrence of PNENs. In both cases, the pathological findings for primary PNEN showed well-differentiated neuroendocrine neoplasms and R0 resection was successfully performed. The Ki-67 index increased with each resection in both cases. Both patients showed long-term survival (10 and 14 years, respectively). Repetitive lymphadenectomy for nodal recurrence of PNENs may improve patient prognosis.